Efektywność w teorii i praktyce na przykładzie wybranych banków spółdzielczych w Polsce - Siudek, Tomasz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
The paper aims to present the efficiency of cooperative banks from the perspective of theory and practice in Poland. The theoretical part reviews the most important definitions of efficiency, its indicators and assessment methods. Empirical study results suggest that the financial efficiency of the cooperative banks in Poland, as measured by ROA and ROE, is statistically significantly impacted by study year and spatial location of bank activity (community and voivodship). Moreover, applying the backward stepwise regression as a method of exploratory analysis, exogenous and endogenous determinants of the cooperative banks efficiency were identified